The archival appraisal and those responsibles the construction of memory in the Brazilian Federal Public Administration - Gomes Do Nascimento, Maria Ivonete; Braga de Oliveira, Eliane (Revista General de Información y Documentación, 2014)
This paper presents partial results of research on archival appraisal held in the Brazilian Federal Public Administration (APF), more specifically in the ministries of the Federal Executive Branch based in Brasilia. Its purpose is to record the theoretical aspects of the archival appraisal and its relation to memory, and to identify the Brazilian legislation and regulations of the National Archives those responsible for the archival appraisal in Brazilian APF. Bibliographical references and legislation relating to the matter were analyzed. A survey data was conducted to verify the compliance of the rules established in the legislation. Different proposals of archival appraisal were identified. It was observed that there is a debate about the role of the archivist as a builder of memory in the practice of archival appraisal. It was also observed that the legislation and the National Archives attach to the Permanent Committees of Documents Appraisal of the public agencies, the responsibility of doing this.
Keywords: Archival appraisal; Archival studies; Archives; Brazilian Federal Public Administration; Memory